2017
DOI: 10.1136/bmjqs-2016-006433
|View full text |Cite
|
Sign up to set email alerts
|

How do hospital boards govern for quality improvement? A mixed methods study of 15 organisations in England

Abstract: BackgroundHealth systems worldwide are increasingly holding boards of healthcare organisations accountable for the quality of care that they provide. Previous empirical research has found associations between certain board practices and higher quality patient care; however, little is known about how boards govern for quality improvement (QI).MethodsWe conducted fieldwork over a 30-month period in 15 healthcare provider organisations in England as part of a wider evaluation of a board-level organisational devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(122 citation statements)
references
References 27 publications
3
105
2
1
Order By: Relevance
“…This lack of confidence in clinical affairs may be part of the reason why many boards focus more on financial governance and meeting external targets than on issues like quality and safety. 17,18 Given the presence of a separate medical staff governance system, this "hands off" approach is likely to be even more pronounced when it comes to physician well-being. And this outlook naturally trickles down to nonclinical administrators at all levels, because it defines what they are accountable for.…”
Section: Barriersmentioning
confidence: 99%
“…This lack of confidence in clinical affairs may be part of the reason why many boards focus more on financial governance and meeting external targets than on issues like quality and safety. 17,18 Given the presence of a separate medical staff governance system, this "hands off" approach is likely to be even more pronounced when it comes to physician well-being. And this outlook naturally trickles down to nonclinical administrators at all levels, because it defines what they are accountable for.…”
Section: Barriersmentioning
confidence: 99%
“…Jones et al 59 have recently constructed a measure of 'QI governance maturity' from working with 15 hospital boards. Consistent with wider organisational literature, they conclude that boards with higher levels of QI maturity had the following characteristics, which were particularly enabled by board-level clinical leaders: l explicitly prioritising QI l balancing short-term external priorities with long-term internal investment in QI l using data for QI, not just for quality assurance l engaging staff and patients in QI l encouraging a culture of continuous improvement.…”
Section: Wider Literature On Quality Improvement Theory Methods and mentioning
confidence: 99%
“…We will apply a board maturity framework developed in previous research, which found that boards with higher levels of maturity in relation to governing for quality improvement were able to effectively balance short-term (external) priorities against long-term (internal) investment in quality improvement and engage staff and patients in the process of change. 21 In order to understand processes of quality improvement beyond board level, especially amongst "clear improvers" that exit SMQ and sustain change, we will use the concepts of absorptive capacity and dynamic capabilities from the strategic management literature to identify any routines or processes that have helped staff -from senior leaders to frontline clinicians -to learn from external information about performance and quality to sustain performance objectives. 22 Absorptive capacity refers to the ability of organisations to acquire and exploit new information and knowledge and successfully transfer it internally -across organisational subunits -to support learning and performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…or performance-focused meetings at divisional level, after securing prior permission, at the 4 'in-depth' sites and gaining individual consent from participants at the time of the meeting. We will use the board quality improvement maturity framework 21 in our observations of boards and other relevant meetings to support analysis of observational data. We will focus on critical quality incidents or service issues where progress in quality improvement appears 'transparently observable' or where improvements are proving especially challenging for the organisations.…”
mentioning
confidence: 99%